KOLABORASI ORANG TUA DENGAN GURU DI SEKOLAH UNTUK MENINGKATKAN PRESTASI SISWA - Maulana, Muhammad Ilham; Yahya, Ilham Muhammad; Suparmi, Suparmi (Universitas Tanjungpura, 2025)
Student learning success is determined not only by the way teachers teach at school, but also by the active role of parents in supporting the learning process. This study aims to measure the impact of collaboration between parents and teachers on improving student achievement. From various articles analyzed, relevant studies published between 2020 and 2025 were selected. The results indicate that regular communication, parental involvement in school activities, and collaboration between teachers and parents in monitoring and guiding students' learning progress significantly contribute to their academic achievement. Thus, organized and structured collaboration between families and schools can increase student learning participation and improve academic and non-academic achievement. The results of this study emphasize the importance of clear communication mechanisms, parental involvement programs, and joint planning between teachers and families to optimize student learning outcomes. Some recommended practical implementations include communication training for teachers and parents, regular meeting schedules, and joint evaluation of learning strategies used.